Penerapan Theory of Constraint pada Kepuasan Kerja Karyawan Rumah Sakit Mata Undaan Surabaya - Selviana Putri Larasati; Setya Haksama (Universitas Airlangga, 2016)
The level of job satisfaction in Undaan Eye Hospital had fluctuating trend since 2012 to 2015. The level of job satisfaction in 2015 was 77,80% that had not reached the target of 80%. The aim of this study was to analize job satisfaction using theory of constraint in Undaan Eye Hospital. This study was an cross sectional observational study. The sample size of this study were 57 employee which were selected using simple random sampling technique (α = 0.05).Health insurance was found as constraint in organizational factor with constraint value of 129. Not only helath insurrance but also career development was found as constraint in organizational factor with constraint value of 132. In the other hand, atmosphere of workplace was found as constraint in work environment with caonstraint value of 141. It can be concluded that efforts should be made to improve employee job satisfaction in Undaan Eye Hospital is to pay attention to health insurance, career development, and workplace atmosphere. Keywords:constraint, job satisfaction, theory of constraint